Biologically Important Areas II for cetaceans within U.S. and adjacent waters – Gulf of Alaska Region - Wild, Lauren A.; Riley, Heather E.; Pearson, Heidi C.; Gabriele, Christine M.; Neilson, Janet L.; Szabo, Andy; Moran, John; Straley, Janice M.; DeLand, Sarah (Frontiers in Marine Science, 2023)
We delineated and scored Biologically Important Areas (BIAs) for cetacean species in the Gulf of Alaska region. BIAs represent areas and times in which cetaceans are known to concentrate for activities related to reproduction, feeding, and migration, and also the known ranges of small and resident populations. This National Oceanic and Atmospheric Association (NOAA)-led effort uses structured expert elicitation principles to build upon the first version of NOAA’s BIAs for cetaceans. Supporting evidence for these BIAs came from aerial-, land-, and vessel-based surveys; satellite-tagging data; passive acoustic monitoring; Indigenous knowledge; photo-identification data; and/or prey studies. A total of 20 BIAs were identified, delineated, and scored for six species: beluga whale (Delphinapterus leucas), fin whale (Balaenoptera physalus), gray whale (Eschrichtius robustus), humpback whale (Megaptera novaeangliae), North Pacific right whale (Eubalaena japonica), and sperm whale (Physeter macrocephalus). Of the 20 total BIAs, there were two small and resident populations, one migratory, and 17 feeding areas; no reproductive BIAs were identified. An additional five watch list areas were identified, a new feature to the second version of BIAs. In addition to more comprehensive narratives and maps, the BIA II products improve upon the first version by creating metadata tables and incorporating a scoring and labeling system which improves quantification and standardization of BIAs within and across regions. BIAs are compilations of the best available science and have no inherent regulatory authority. They have been used by NOAA, other federal agencies, and the public to support planning and marine mammal impact assessments, and to inform the development of conservation measures for cetaceans.